Love and Revolution in the Twentieth-Century Colonial and Postcolonial World
XXII, 366 p. 24 illus.
Keywords: This book addresses emancipatory narratives from two main sites in the colonial world, the Indian and southern African subcontinents. Exploring how love and revolution interrelate, this volume is unique in drawing on theories of affect to interrogate histories of the political, thus linking love and revolution together. The chapters engage with the affinities of those who live with their colonial pasts: crises of expectations, colonial national convulsions, memories of anti-colonial solidarity, even shared radical libraries. It calls attention to the specific and singular way in which notions of ‘love of the world’ were born in a precise moment of anti-colonial struggle: a love of the world for which one would offer one’s life, and for which there had been little precedent in the history of earlier revolutions. It thus offers new ways of understanding the shifts in global traditions of emancipation over two centuries. G. Arunima is Professor in theCentre for Women’s Studies at Jawaharlal Nehru University, India. She has researched and published on both historical and modern contexts in India, focusing particularly on cultural, visual and material texts, and rethinking the politics of the contemporary. Patricia Hayes is a National Research Foundation and South African Research Chair of Visual History and Theory at the Centre for Humanities Research at the University of the Western Cape, South Africa. She has published extensively on history and colonial and documentary photography in southern Africa. Premesh Lalu is Convenor of the Communicating the Humanities project at the Centre for Humanities Research at the University of the Western Cape, South Africa. As one of the founding directors of the Centre for Humanities Research, he has raised the profile of the humanities both in the university and nationally. His publications address colonial archives, violence, and more recently, aesthetics and the technical becoming of the human.